Enhancing Consumer Protection in Electronic Transactions in Indonesia - Zaidah Nur Rosidah; Lego Karjoko (Sriwijaya Law Review, 2025)
Technological advancements have significantly facilitated electronic transactions, making business interactions faster and more convenient. However, these developments also introduce risks, especially for consumers, as electronic transactions can lead to significant financial losses if not handled carefully. This study proposes effective legal protections for consumers to prevent such losses and ensure proper compensation in electronic business transactions. This research employs a normative legal methodology, utilizing both a statutory and conceptual approach. The statutory approach analyses laws and regulations governing electronic transactions, while the conceptual approach applies Richard Posner's Economic Analysis of Law theory to assess the efficiency of consumer protection mechanisms. Data was gathered through a literature review of primary and secondary legal sources, and conclusions were drawn using deductive reasoning. The Economic Analysis of Law theory was the major premise, with relevant laws and regulations forming the minor premise. The findings reveal two main conclusions. First, while existing laws such as the Consumer Protection Law, the ITE Law, PP PMSE, PP PSTE, and Regulation of the Minister of Trade Number 31 of 2023 provide basic consumer protection by sanctioning businesses that offer mismatched products, reclaiming consumer rights is not straightforward. Second, to mitigate potential losses in electronic transactions, a validation process for business actors is necessary before they offer products, and Electronic System Trading Providers (PPMSE) must establish an efficient mechanism for compensating consumer losses. This study highlights the need for a more robust and accessible framework to protect consumers in electronic business transactions, ensuring that legal recourse is both efficient and effective.